An UXor among FUors: extinction related brightness variations of the young eruptive star V582 Aur - Ábrahám, Péter; Hajdu, Gergely (Arxiv, 2017)
V582 Aur is an FU Ori-type young eruptive star in outburst since $\sim$1985. The eruption is currently in a relatively constant plateau phase, with photometric and spectroscopic variability superimposed. Here we will characterize the progenitor of the outbursting object, explore its environment, and analyse the temporal evolution of the eruption. We are particularly interested in the physical origin of the two deep photometric dips, one occurred in 2012, and one is ongoing since 2016. We collected archival photographic plates, and carried out new optical, infrared, and millimeter wave photometric and spectroscopic observations between 2010 and 2017, with high sampling rate during the current minimum. Beside analysing the color changes during fading, we compiled multiepoch spectral energy distributions, and fitted them with a simple accretion disk model. Based on pre-outburst data and a millimeter continuum measurement, we suggest that the progenitor of the V582 Aur outburst is a low-mass T Tauri star with average properties. The mass of an unresolved circumstellar structure, probably a disk, is 0.04 M$_{\odot}$. The optical and near-infrared spectra demonstrate the presence of hydrogen and metallic lines, show the CO bandhead in absorption, and exhibit a variable H$α$ profile. The color variations strongly indicate that both the $\si